Abancay avenue: Between "Urban progress" and preservation of historic buildings - Barrera Camarena, Henry (2025)
The article deals with the significance of the widening of Abancay Street, located in the historic center of Lima, in the 1950s, in order to make it an avenue and thus decongest vehicular traffic in that part of the capital. The dilemma that arose between prioritizing what was understood as urban progress, with a view to understanding that in the coming years this sector would be an important link between the center of Lima and the rest of the city, and preserving the colonial and republican architectural heritage, is analyzed. For this purpose, the Municipal Bulletin, the notes prepared by the local newspapers and other official media were reviewed, which showed their position, contrary or in favor of the widening. In the end, it will be seen that in spite of the questionings that arose in favor of the conservation, the demolishing pillory ended up being imposed.